Description of a new subterranean breeding brown frog (Ranidae: Rana) from Japan - Eto, Koshiro; Matsui, Masafumi; Sugahara, Takahiro (Zootaxa, 2022)
Taxonomic relationship of two forms of Rana tagoi, a brown frog endemic to Japan, is assessed. Based on morphological and bioacoustical comparisons, as well as molecular analysis, we consider the large-form-lineage as true R. tagoi, and describe the small-form-lineage as Rana kyoto sp. nov. The new species and R. tagoi occur sympatrically in many places around the Kinki District, although the former can be distinguished from the latter by smaller body size, more developed dark marking on ventral side of legs, less developed toe webs, and advertisement call with fewer notes and lower dominant frequency. Rana kyoto sp. nov. sympatric with R. tagoi show smaller body size than the allopatric ones, whereas R. tagoi sympatric with the new species show larger body size than the allopatric ones, suggesting that the character displacement of body size occurs between the two species around the type locality of Rana kyoto sp. nov.